Efficacy and mechanism of intermittent fasting in metabolic associated fatty liver disease based on ultraperformance liquid chromatography-tandem mass spectrometry - Deng, Jiang; Feng, Dandan; Jia, Xiaoli; Zhai, Song; Liu, Yixin; Gao, Ning; Zhang, Xin; Li, Mei; Lu, Mengnan; Liu, Chenrui; Dang, Shuangsuo; Shi, Juanjuan (Frontiers in Nutrition, 2022)
Objectives Drug treatment of metabolic associated fatty liver disease (MAFLD) remains lacking. This study analyzes the efficacy and mechanism underlying intermittent fasting combined with lipidomics. Methods Thirty-two male rats were randomly divided into three groups: Normal group, administered a standard diet; MAFLD group, administered a 60% high-fat diet; time-restricted feeding (TRF) group, administered a 60% high-fat diet. Eating was allowed for 6 h per day (16:00–22:00). After 15 weeks, liver lipidomics and other indicators were compared. Results A total of 1,062 metabolites were detected. Compared with the Normal group, the weight, body fat ratio, aspartate aminotransferase, total cholesterol, low-density cholesterol, fasting blood glucose, uric acid, and levels of 317 lipids including triglycerides (TG) (17:0−18:1−20:4) were upregulated, whereas the levels of 265 lipids including phosphatidyl ethanolamine (PE) (17:0−20:5) were downregulated in the MAFLD group (P < 0.05). Compared with the MAFLD group, the weight, body fat ratio, daily food intake, and levels of 253 lipids including TG (17:0−18:1−22:5) were lower in the TRF group. Furthermore, the levels of 82 lipids including phosphatidylcholine (PC) (20:4−22:6) were upregulated in the TRF group (P < 0.05), while serum TG level was increased; however, the increase was not significant (P > 0.05). Enrichment analysis of differential metabolites showed that the pathways associated with the observed changes mainly included metabolic pathways, regulation of lipolysis in adipocytes, and fat digestion and absorption, while reverse-transcription polymerase chain reaction showed that TRF improved the abnormal expression of FAS and PPARα genes in the MAFLD group (P < 0.05). Conclusion Our results suggest that 6 h of TRF can improve MAFLD via reducing food intake by 13% and improving the expression of genes in the PPARα/FAS pathway, thereby providing insights into the prevention and treatment of MAFLD.